Farhang-i kalām-i Mīr - ʿAbd-ar-Rašīd (Dillī Kitāb Ghar, 2013)
Glossary of words used by Mīr Taqī Mīr, 1722-1810, Urdu poet, in his poems; in the light of Chirāgh-i hidāyat by Sirājuddīn ʿAlī Ḵẖān Ārzū,1689-1756, Urdu and Persian poet
Includes bibliographical references. - In arab. Schrift, Urdu. - Title on t.p. verso in roman: Farhang-e-kalam-e-Meer
Keywords: Konkordanz; Mīr; Mīr Taqī 1722-1810